Comparative Analysis of the Level of Knowledge-based Part of Economies in European Union Countries with KAM Methodology - Strożek, Piotr (Comparative Economic Research. Central and Eastern Europe, 2013)
The article presents regional classification of EU countries according to the knowledge development of economy, which in these days is treated as fundamental factor of international competitiveness. This differentiation created with Knowledge Economy Index (KEI) and Knowledge Index (KI), which are use by The World Bank in Knowledge Assessment Methodology (KAM). In the analysis used four main pillars (i.e. The Economic Incentive and Institutional Regime, The Innovation System, Education and Human Resources, Information and Communication Technology), which showed relation between individual components. The purpose of this article is to identify disparities in the use of knowledge in socio-economic life in the EU countries. This research was conducted with use of the cluster analysis (tools belonging to multidimensional comparative analysis).